Highly effective teachers of vulnerable students practice transcending theory - Poplin, Mary S. 1951-; Bermudez, Claudia 1973- (Peter Lang, 2019)
"In these pages lie the quintessential details of highly effective teachers working with students who live in poverty inside our public schools and community colleges. It also contains the words and actions of the teachers that can inspire and direct any current or future teacher who wants to be great and be a part of inspiring young people to fulfill their potential. This is the grist we need to spark a reinvigorated critical national conversation about what it takes to really have highly effective teachers in low-income public schools and whether we have the moral courage to work as hard as they do to make educational equity a reality in our nation"--Provided by publisher.